Instability in Flow Boiling in Microchannels - Saha, Sujoy Kumar; Celata, Gian Piero (SpringerBriefs in Thermal Engineering and Applied Science, 2016)
This Brief addresses the phenomena of instability in flow boiling in microchannels occurring in high heat flux electronic cooling. A companion edition in the SpringerBrief Subseries on Thermal Engineering and Applied Science to "Critical Heat Flux in Flow Boiling in Microchannels," and "Heat Transfer and Pressure Drop in Flow Boiling in Microchannels,"by the same author team, this volume is idea for professionals, researchers, and graduate students concerned with electronic cooling.